Geo-environmental problem of snow avalanche defensive structures in mudstone zones, Niigata Prefecture, Japan - Aoyama, K.; Bhattarai, P.; Fukuda, M.; Oku, J.; Sakai, T. (Journal of Nepal Geological Society, 2002)
Fence-type defensive structures are very common on highway hillsides in Japan. They are constructed to protect the highway mainly from snow avalanche. Initially, these structures behave well. However, as the time lapses, the foundation of these well designed structures weakens and collapses. The situation is further aggravated by the static load of accumulated thick snow cover behind them. As mudstone is the dominant rock type in the Niigata Prefecture, it is a challenging task for geotechnical engineers to cope with such a severe geo-environmental problem. Although the mudstone exhibits a high strength while it is dry and fresh, it becomes quite unstable after sometime. When it comes in contact with water and atmosphere repeatedly, it starts weathering. Consequently, its shear strength is reduced and cannot resist the imposed shear stress and moment, and ultimately fails. For the laboratory investigation, mudstone blocks of various sizes were collected from the two typical mudstone areas: the Matsunoyama area and Nagaoka area in the Niigata Prefecture. These samples were sub merged and then dried alternately for several cycles. The particle size analysis of the weathered material showed that the proportion of fine particles increased with the degree of weathering. The laboratory tests of these samples exhibited a decrease in shear strength with an increasing degree of saturation. The periodic swelling and contraction of the clay fraction leads to volume change of foundation inducing its further weathering.